Additive Links on Multiple Access (ALOHA) Method to LoRaWAN Satellite-based communication - Adi, Puput Dani Prasetyo; Stekelorom, Kevin; Vasista, Tatapudi Gopikrishna (Universitas Muhammadiyah Yogyakarta, 2025)
LoRaWAN communication systems continue to improve with various advantages that continue to improve, for example, terrestrial LoRaWAN which increases satellite communication, and improves performance in terms of wider range, up to> 100 km. However several problems arise, including multiple end-node connection conditions. Not only point-to-point but already multi-point which causes several obstacles including data collisions, thus requiring several methods such as ADR (Adaptive Data Rate) or ALOHA (Additive Links on Multiple Access). The role of ALOHA is to be able to build an inter-node communication system that can prevent data collisions. In this case, ALOHA is used to improve the performance of IoT-LoRaWAN on satellite infrastructure. Some of the simulation components of this research lie in the data transmission protocol mechanism and collision management strategy, as well as spectrum efficiency in essential satellite-based LoRaWAN networks. The core of the research is how to reduce signal interference and optimize power consumption. Hopefully, ALOHA can be used as an effective method to build LoRaWAN Satellite-based IoT in the future. The future applications are for tracking, environmental monitoring, and disaster warning systems.